2019
DOI: 10.1002/humu.23847
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of functionally assessed GHRHR mutations to idiopathic isolated growth hormone deficiency in patients without GH1 mutations

Abstract: Isolated growth hormone deficiency (IGHD) is a rare condition mainly caused by mutations in GH1. The aim of this study was to assess the contribution of GHRHR mutations to IGHD in an unusually large group of patients. All GHRHR coding exons and flanking intronic regions were sequenced in 312 unrelated patients with nonsyndromic IGHD. Functional consequences of all newly identified missense variants were assessed in vitro (i.e., study of the expression of recombinant GHRHRs and their ability to activate the cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Especially patients with mutations in the same gene cannot be fully diagnosed GHD, such as IDS and GHRHR . Recent genotype-phenotype correlation study in 24 patients with GHRHR mutation found that the different mutation types could not fully explain the phenotypic discrepancy ( 32 ), which is consistent with our findings. In addition, the inconsistent severity of phenotypes was also observed in two IDS patients with the same mutation.…”
Section: Discussionsupporting
confidence: 86%
“…Especially patients with mutations in the same gene cannot be fully diagnosed GHD, such as IDS and GHRHR . Recent genotype-phenotype correlation study in 24 patients with GHRHR mutation found that the different mutation types could not fully explain the phenotypic discrepancy ( 32 ), which is consistent with our findings. In addition, the inconsistent severity of phenotypes was also observed in two IDS patients with the same mutation.…”
Section: Discussionsupporting
confidence: 86%
“…Presumably, naturally occurring mutations may disrupt the disulfide bonds (C64G and C112Y) or the conserved D-W-R/K-W motif (R94Q/L/W), thereby destabilizing the stability of ECD and preventing GHRH recognition. Indeed, our MD simulation and functional studies suggest that the IGHD-associated mutation R94Q 32 breaks the salt bridge with D60, increases the flexibility of the ECD, decreases the area of GHRH–GHRHR interface, and reduces GHRH-induced cAMP accumulation (Fig. 4b and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 85%
“…In a Dutch cohort of 89 patients, five GH1 variants (missense and splice sites variants) were diagnosed in 9% of the patients [24]. A broad study of the GHRHR gene was undertaken by Cohen et al [25], who studied 312 French patients with GHD, but who lacked the GH1 variant. They identified a total of 22 variants (17 novel) in GHRHR in 26 patients, including splice site and frameshift variants, intronic deletions, and missense and nonsense substitutions.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed analysis of the identified GHRHR variants showed that twenty variants were defined as highly probable disease-causing (loss-of-function) mutations, while the effect on protein function was uncertain for another two variants. This study has shown that variants in the GHRHR gene are a second cause of GHD, besides GH1 variants [ 25 ].…”
Section: Discussionmentioning
confidence: 99%